How India’s agrifood supply chains fared during the COVID-19 lockdown, from farm to fork - Narayanan, Sudha (International Food Policy Research Institute, 2022)
In response to the COVID-19 pandemic, the Indian government imposed a stringent national lockdown from March 24 to May 31, 2020, which caused severe disruptions across agrifood supply chains from “farm to fork.” The government was consistently one step behind in terms of preventing these problems (Narayanan and Saha 2020b).